Production and characterisation of four Joubert syndrome patient-derived induced pluripotent stem cell (iPSC) lines with mutations in either RPGRIP1L or CPLANE1 genes - L. Pollara; E. de Gregorio; V. Buonofiglio; L. Bianca; T. Stellato; M. Brusa; E. De Gasperi; A. Ardissone; G. Zanni; R. Battini; S. Briuglia; V. Sottile; et al. (Stem Cell Research)
Four iPSC lines were generated from patients with Joubert syndrome, two carrying compound heterozygous variants in the RPGRIP1L gene (c.2050C > T/c.2304 + 1G > T for one line, c.751C > T/c.1679C > T for the other) and two harbouring homozygous variants in the CPLANE1 gene (c.8137_8138insT for one line, c.4634G > A for the other). Dermal fibroblasts from patients were reprogrammed using the Sendai virus method and the resulting iPSC lines, confirmed to show the same STR profile as parental fibroblasts, displayed a normal karyotype, the expression of undifferentiated PSC markers (OCT4, SOX2, SSEA4 and NANOG) and the ability to differentiate into derivatives of the three germ layers in vitro.